Relationship between macrophage phenotype and kidney survival in patients with lupus nephritis - Ozcan Uzun; Cihan Heybeli; Fatma Sema Anar Kutlu; Evrim Atmaca; Filiz Yıldırım; Caner Cavdar; Sulen Sarioglu (Nefrología (English Edition))
Aims: To determine the possible relationship between macrophage phenotypes and the progression of kidney disease in patients with lupus nephritis (LN). Methods: Using immunohistochemistry, CD68+ and CD163+ cells were counted per glomerulus and per high-power field in the tubulointerstitium. Progression was defined as a doubling of the serum creatinine level and/or progression to end-stage kidney disease. Results: Among the 21 patients, 52% had class III or IV LN. During the median follow-up of 88 months, 5 (23.8%) patients experienced progression. In terms of clinical and pathological markers, the only significant difference between progressors and nonprogressors was the number of interstitial CD163+ cells (median 4 versus 2.4, respectively; p = 0.025). A cutoff value of 2.7 for the mean number of CD163+ cells in the interstitium yielded a sensitivity of 80% and specificity of 75% for progression. The estimated median time to progression among patients with ≥2.7 CD163+ cells was shorter (median 136 versus 202 months, p = 0.023). A greater number of CD163+ cells in the kidney interstitium was associated with the progression of kidney disease (HR 2.88, 95% CI 1.22–6.80; p = 0.016). Class III–IV LN was associated with a higher median number of glomerular CD163+ cells (OR 1.96, 95% CI 1.1–3.49, p = 0.023). Endocapillary hypercellularity and extracapillary proliferation were associated with greater number of CD163+ cells in the glomerular area. Among patients with class III-IV LN, the number of interstitial CD68+ cells was greater in those who experienced progression of kidney disease (p = 0.012). Conclusion: A greater number of CD163+ cells in the kidney interstitium was associated with the progression of kidney disease in patients with LN, while a greater number of CD68+ cells in the interstitium was associated with progression in the subgroup of patients with class III-IV LN. Resumen: Objetivos: Determinar la posible relación entre los fenotipos de macrófagos y la progresión de la enfermedad renal en pacientes con nefritis lúpica (NL). Métodos: Mediante inmunohistoquímica, se contaron células CD68+ y CD163+ por glomérulo y por campo de gran aumento en el tubulointersticio. La progresión se definió como una duplicación del nivel de creatinina sérica o progresión a enfermedad renal terminal. Resultados: Entre los 21 pacientes, el 52% tenía NL de clase iii o iv. Durante la mediana de seguimiento de 88 meses, 5 (23,8%) pacientes experimentaron progresión. En términos de marcadores clínicos y patológicos, la única diferencia significativa entre los pacientes que progresaron y los que no progresaron fue el número de células intersticiales CD163+ (mediana de 4 frente a 2,4, respectivamente; p = 0,025). Un valor de corte de 2,7 para el número medio de células CD163+ en el intersticio arrojó una sensibilidad del 80% y una especificidad del 75% para la progresión. El tiempo medio estimado hasta la progresión entre los pacientes con ≥2,7 células CD163+ fue más corto (mediana de 136 frente a 202 meses; p = 0,023). Un mayor número de células CD163+ en el intersticio renal se asoció con la progresión de la enfermedad renal (HR 2,88; IC 95%: 1,22-6,80; p = 0,016). La NL de clase iii-iv se asoció con un mayor número medio de células CD163+ glomerulares (OR 1,96; IC 95%: 1,1-3,49; p = 0,023). L’ipercellularità endocapillare e la proliferazione extracapillare sono state associate a un maggior numero di cellule CD163+ nell’area glomerulare. Entre los pacientes con NL de clase iii-iv, el número de células CD68+ intersticiales fue mayor en aquellos que experimentaron progresión de la enfermedad renal (p = 0,012). Conclusión: Un mayor número de células CD163+ en el intersticio renal se asoció con la progresión de la enfermedad renal en pacientes con NL, mientras que un mayor número de células CD68+ en el intersticio se asoció con la progresión en el subgrupo de pacientes con NL de clase iii-iv.